The Moderation Effect of Work Discipline: Leadership Style on the Statistics Indonesia Employee Performance in Lamongan - Riana Prastiwi Handayani; Adi Lukman Hakim (Journal of Leadership in Organizations, 2022)
Introduction/Main Objectives: This study focused on human resource management at The Statistics of Lamongan Regency, where employees need reliable and competent leadership. Leadership is categorized as an empowerment concept when leaders share directions, support systems, are friendly, synergize, and provide exemplary examples to their subordinates. Background Problems: Through scientific ways, this study attempted to respond to the research questions; 1)Does leadership style have a significant effect on employee performance, 2) Does leadership style and work discipline have a significant effect on employee performance, 3) Does employee work discipline moderate the influence of leadership style on employee performance? Novelty:The current study highlights the indicator of leadership styles from Michigan university’s model, which was infrequently used in this type of research. Whereas, this angle seems fit for seeking leader from both directions; task and relationship behaviour, to find out why employee performance reaches sufficient high category. Besides, another differentiating element is a research approach of moderating variable of discipline, to know of those that strengthen or weaken performance resulting from the leadership style. Research Methods: The survey design administered the questionnaire, interviews, and observation to the target samples. The data was then analyzed using descriptive analysis and Moderated Regression Analysis. Finding/Results: The results show that leadership style affects employee performance, leadership style, and work discipline positively and significantly. Work discipline can moderate leadership style on employee performance. Conclusion: Leaders can select any leadership style,  but they must remain aware of task and relationship behavior. This study has many limitations; hence, the future researcher can apply other leadership styles under different conditions